2021
DOI: 10.3390/lubricants9090088
|View full text |Cite
|
Sign up to set email alerts
|

CFD Analysis of Journal Bearing with a Heterogeneous Rough/Smooth Surface

Abstract: In the present study, a computational investigation into acoustic and tribological performances in journal bearings is presented. A heterogeneous pattern, in which a rough surface is engineered in certain regions and is absent in others, is employed to the bearing surface. The roughness is assumed to follow the sand-grain roughness model, while the bearing noise is solved based on broadband noise source theory. Three types of heterogeneous rough/smooth journal bearings exhibiting different placement and number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Many studies have been conducted on the drawbacks that a rough surface has on the lubrication regime, while some researchers even investigated certain conditions under which a surface roughness arrangement could be beneficial. Tauviqirrahman et al [4,5] studied the possibility of utilizing a heterogenous rough/smooth surface profile, which would provide superior tribological properties compared to the equivalent homogenous smooth or rough bearing.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been conducted on the drawbacks that a rough surface has on the lubrication regime, while some researchers even investigated certain conditions under which a surface roughness arrangement could be beneficial. Tauviqirrahman et al [4,5] studied the possibility of utilizing a heterogenous rough/smooth surface profile, which would provide superior tribological properties compared to the equivalent homogenous smooth or rough bearing.…”
Section: Introductionmentioning
confidence: 99%
“…According to Sahu and Sharma, 23 the minimum fluid film thickness, lubricant flow, and fluid film damping coefficients are all improved by the three‐dimensional irregularities on the bearing surface. Tauviqirrahman et al 24 reported that the heterogeneous rough/smooth bearings may bear more load and produce less noise than conventional bearings. According to Bangotra and Sharma, 25 the influence of waviness on the bearing surface increases load capacity and, lowers the friction coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that a textured bearing operating at low rotational speeds resulted in an increase in the load-carrying capacity and reduction in frictional losses in comparison to an untextured bearing working in similar operating conditions. Tauviqirrahman et al 29 performed a CFD analysis on hydrodynamic journal bearings having heterogeneous rough/smooth surfaces. They have modeled the bearing surface using an alternate radial zone of rough and smooth surfaces.…”
Section: Introductionmentioning
confidence: 99%